Choosing TBM for Tabriz subway using multi criteria method - Edalat, Kamaladdin; Vahdatirad, Mohammad Javad; Ghodrat, Hadi; Firouzian, Sarah; Barari, Amin (Journal of Civil Engineering and Management, 2010)
The world of underground engineering and construction has acquired a wide‐ranging and high‐level experience on tunnel construction with Tunnel Boring Machines (TBM) and nowadays remarkable progresses are traceable in the number of tunnels that are becoming longer, going deeper, and growing larger in diameter and in other words becoming more difficult to realize. Tabriz‐one of the big cities in northern west of Iran has four subway lines which are under construction or investigation. The phase1 design of Tabriz urban railway line 2 (TURL2) has completely been done. Method statement of this line in the length of about 20 km and much interference due to tunneling in urban area dictates the application of TBM. Two kinds of TBM such as EPB (earth pressure balance) and SS (slurry shield) are usually used for urban areas. In this paper, the process of choosing TBM for TURL2 using MCA method (Multi Criteria Analysis) is expressed. Generally in this method some technical, economical and environmental parameters affected the TBM type are identified and taken into account by assigned weights related to the case study. Finally the results show that EPB‐TBM will be more appropriate choice for TURL2 excavation.First Published Online: 10 Feb 2011